2015
DOI: 10.1063/1.4918780
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of electron-hole asymmetry in nanoparticles of Nd1−xCaxMnO3(x=0.6,0.4): magnetization and electron paramagnetic resonance evidence

Abstract: We study and compare magnetic and electron paramagnetic resonance behaviors of bulk and nanoparticles of Nd1−xCaxMnO3 in hole doped (x=0.4;NCMOH) and electron doped (x=0.6;NCMOE) samples. NCMOH in bulk form shows a complex temperature dependence of magnetization M(T), with a charge ordering transition at ∼250 K, an antiferromagnetic (AFM) transition at ∼150 K, and a transition to a canted AFM phase/mixed phase at ∼80 K. Bulk NCMOE behaves quite differently with just a charge ordering transition at ∼280 K, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…For the half doped compound, x = 0.5 composition, the T N is observed at 105 K and a sharp increase in FC curve below 80 K is noticed, which can be accounted to the ordering of Nd sublattices. The results suggest that, upon the substitution of 30-50% of Ca content, the compound changes from pseudo CE-type AFM to CE-type AFM, which is corroborated with earlier reports [21,[34][35][36][37][38][39].…”
Section: Magnetic Characterizationssupporting
confidence: 91%
See 2 more Smart Citations
“…For the half doped compound, x = 0.5 composition, the T N is observed at 105 K and a sharp increase in FC curve below 80 K is noticed, which can be accounted to the ordering of Nd sublattices. The results suggest that, upon the substitution of 30-50% of Ca content, the compound changes from pseudo CE-type AFM to CE-type AFM, which is corroborated with earlier reports [21,[34][35][36][37][38][39].…”
Section: Magnetic Characterizationssupporting
confidence: 91%
“…Upon further increase of Ca content, an additional transition at higher temperature is noticed (shown in figures 3(c) and (d)), which is understood as a charge ordering (CO) transition in accordance with the earlier reports [21]. It is reported that the hole and electron-doped manganites have a tendency of Mn 3+ and Mn 4+ cations to charge and orbital ordering [21]. In the inset to figure 3, M × T versus T is plotted to check the presence of any residual CO in the compounds.…”
Section: Magnetic Characterizationssupporting
confidence: 91%
See 1 more Smart Citation